Morphological and anatomical studies of the newly recorded Rhus chinensis Mill. (Anacardiaceae) from Turkey (Bangladesh Journal of Plant Taxonomy, 2018)
Rhus chinensis Mill. (Anacardiaceae) has been reported as a new record for the flora of Turkey. Detailed morphological description and leaf anatomical properties are provided. Capitate glandular and nonglandular trichomes, and also epicuticle hairs have been observed in the leaf surfaces of R. chinensis. Fruit micromorphology and chromosome number of this species have also been evaluated.Bangladesh J. Plant Taxon. 25(1): 71-78, 2018 (June)